Confinement of Reinforced-Concrete Columns with NonCode Compliant Confining Reinforcement plus Supplemental Pen-Binder - Kristianto, Anang; Imran, Iswandi; Suarjana, Made; Pane, Ivindra (ITB Journal Publisher, LPPM ITB, 2012)
Abstract. One of the important requirements for earthquake resistant building related to confinement is the use of seismic hooks in the hoop or confining reinforcement of reinforced-concrete column elements. However, installation of a confining reinforcement with a 135-degree hook is not easy. Therefore, in practice, many construction workers apply a confining reinforcement with a 90-degree hook (non-code compliant). Based on research and records of recent earthquakes in Indonesia, the use of a non-code compliant confining reinforcement for concrete columns produces structures with poor seismic performance. This paper presents a study that introduces an additional element that is expected to improve the effectiveness of concrete columns confined with a non-code compliant confining reinforcement. The additional element, named a pen-binder, is used to keep the non-code compliant confining reinforcement in place. The effectiveness of this element under pure axial concentric loading was investigatedcomprehensively.The specimens tested in this study were 18 concrete columns,with a cross-section of 170 mm x 170 mm and a height of 480 mm. The main test variables were the material type of the pen-binder, the angle of the hook, and the confining reinforcement configuration.The test results indicate that adding pen -binders can effectively improve the strength and ductility of the column specimens confined with a non-code compliant confining reinforcement.